Uma arquitetura de comunicação com mecanismos para atendimento dos requisitos das redes elétricas inteligentes rurais - Prade, Lúcio Renê (2020)
The current transformation scenario in power distribution networks signals the need for alternative solutions in communication systems employed in making them intelligent. As a premise, these alternatives should be easy to implement and affordable to allow their adoption in rural distribution networks, where the use of other technologies, such as mobile, is often not available. The increasing expansion of distributed generation associated with the maintenance of energy quality standards justifies the insertion of digital technologies in rural networks to achieve these goals. In this sense, this study introduces a new communication architecture with the Mesh topology, based on LoRa technology. The architecture adapts packet prioritization and multiple channel mechanisms to ensure the communication requirements necessary for the services. Several applications and protocols of a Smart Grid can coexist in the same communication system. The deployment of the architecture gave rise to a routing protocol adapted to the limitations of the radio technology used. Moreover, this study generated a co-simulation tool to evaluate and measure the automation projects in distribution networks, which aim to use the proposed system, besides the creation of hardware prototypes used in the implementation of the communication system. The gains of the proposed architecture can be observed when compared to traditional LPWAN networks and cellular technologies. The robustness of the system was evaluated with average latency measurement within the acceptable range for DNP3, Modbus, and NBR14522 applications. These indices are guaranteed by the packet prioritization and the multiple channels mechanisms. Furthermore, by applying the various channels mechanism, packet collision rates decreased by an average of 25%. The results prototyped show its potential employment in the management of intelligent rural distribution systems.